Development of a Chemo-Entrepreneurship-Oriented PjBL-STEM Interactive e-Module on Buffer Solutions to Improve Students’ Creative Thinking Skills - Febry Aryanti Huta Uruk; Rayandra Asyhar; Zurweni (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2026)
This study uses the Research and Development (R&D) method with the Lee & Owens model. Participants of this study were grade XI high school students. Data were collected through interviews, questionnaires, and creative thinking ability tests, then analyzed using the average score, paired T-test, and N-Gain test. The results of the study showed that the developed e-module was very feasible based on the validation of material experts with an average score of 4.42 and validation of media experts with an average score of 4.7 in the very good category, and obtained very good responses from teachers with an average score of 4.44 and students with a percentage of one-on-one trials of 89.33%, small group trials of 87.11% and field trials of 87.29%. The effectiveness test showed a t-count value of 18.286 with Sig. (2-tailed) <0.05 and N-Gain of 0.6836 (quite effective) and an increase in pretest-posttest of 32.76%. It can be concluded that the interactive e-module is valid, practical, and moderately effective in improving senior high school students' creative thinking skills on the topic of buffer solutions.